A novel bird-shape broadband piezoelectric energy harvester for low frequency vibrations - Yu, Han (2023)
This work presents a novel bird-shaped broadband piezoelectric energy harvester based on a two-DOF crossed beam for low-frequency environmental vibrations. The harvester features a cantilever mounted on a double-hinged beam, whose rotating motions effectively diminish its natural frequencies. Numerical simulation based on the finite element method is conducted to analyze the modal shapes and the harmonic response of the proposed harvester. Prototypes are fabricated and experiments are carried out by a testing system, whose results indicate a good agreement with the simulation. The multi-frequency energy harvesting is achieved at the first-, second-, and fifth-order resonances. In particular, the proposed harvester demonstrates the remarkable output characteristics of 9.53 mW and 1.83 mW at frequencies as low as 19.23 HZ and 45.38 Hz, which are superior to the majority of existing energy harvesters. Besides, the influences of key parameters on the harvesting performance are experimentally investigated to optimize the environmental adaptability of the harvester. This work provides a new perspective for efficiently harvesting the low-frequency vibration energy, which can be utilized for supplying power to electronic devices.